Plasmonic spin-Hall effect of propagating surface plasmon polaritons in Ni80Fe20 microstructures. (2nd September 2021) - Paleschke, Maximilian; Chiang, Cheng-Tien; Brandt, Liane; Liebing, Niklas; Woltersdorf, Georg; Widdra, Wolf
Abstract: Photoexcitation and shaping of a propagating surface plasmon polariton (SPP) on silver and gold microstructures are well established and lead to the discovery of the plasmonic spin-Hall effect recently. Whereas silver is often the material of choice due to its exceptional low plasma frequency and weak damping, similar observations have not been reported for ferromagnetic metals. In this work, we report on propagating SPPs on Ni80 Fe20 microstructures imaged by photoemission electron microscopy (PEEM) in combination with a tunable femtosecond laser system at MHz repetition rate. Circular dichroic (CD) images in threshold PEEM show clear edge-induced SPPs with sub-micrometer wavelength and propagation length of about 3.5 μ m. Analysis of the interference patterns as well as the coupling of the optical spin angular momentum to the observed fringe fields reveal propagation characteristics exclusive to evanescent waves and the presence of the plasmonic spin-Hall effect. Our work provides direct evidence that many materials with a high plasma frequency allow for excitation and observation of propagating SPPs at the dielectric/metal interface via CD PEEM imaging, enabling magnetoplasmonic investigation of common ferromagnets on nanometer length and femtosecond time scales. Video Abstract: Video Abstract: Plasmonic spin-Hall effect of propagating surface plasmon polaritons in Ni80 Fe20 microstructures